2017
DOI: 10.4172/2161-0940.1000259
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurement of Weight for Assessment of Nutritional Status of Anganwadi Children in Urban Mangalore - A Cross Sectional Study

Abstract: Background and objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…4 In a study conducted on Various Anthropometric Methods of Assessment of Nutritional Status in Under Five Children by Pandve HT, Singru SA was found that 49% were normal and 49% were mildly malnourished according to Gomez classifiaction for weight for age. 5,6 In this study it was observed that 32% of children were moderately underweight and 4% were severely underweight.…”
Section: Discussionmentioning
confidence: 69%
“…4 In a study conducted on Various Anthropometric Methods of Assessment of Nutritional Status in Under Five Children by Pandve HT, Singru SA was found that 49% were normal and 49% were mildly malnourished according to Gomez classifiaction for weight for age. 5,6 In this study it was observed that 32% of children were moderately underweight and 4% were severely underweight.…”
Section: Discussionmentioning
confidence: 69%
“…in their study found the prevalence of stunting, underweight, and wasting to be 45.52%, 34.14%, and 35.52%, respectively. [ 10 ] Studies from Gadag[ 17 ] and Mangalore[ 18 ] also reported the prevalence of stunting ranged from 35% to 55%, underweight ranged from 24% to 60%, and wasting ranged from 11% to 60%. A study by Bhavsar reported 59.8% of children suffered from malnutrition.…”
Section: Discussionmentioning
confidence: 99%